Numerical modeling and validation of earthquake soil structure interaction: a 12-story building in Ventura, California - Yang, Han; Wang, Hexiang; Jeremić, Boris (Frontiers in Built Environment, 2023)
Presented is a validation study for high fidelity numerical modeling of earthquake soil structure interaction (ESSI) for a building, hotel structure in Ventura, California. A detailed finite element (FE) model of the ESSI system, featuring the 12-story concrete structure, pile group foundation, and underlying soil, is developed using the Real-ESSI Simulator (Jeremić et al., 2022a). The domain reduction method (DRM) (Bielak et al., 2003;Yoshimura et al., 2003) is used to apply seismic loads, in this case the 1994 Northridge earthquake motions. Direct comparison between simulation results and California Strong Motion Instrumentation Program (CSMIP) recordings shows a high level of agreement in acceleration and displacement responses at all instrumented locations. Sensitivity study on a number of modeling choices and analysis parameters is conducted to investigate controlling factors for the ESSI response. For example, the soil-structure interaction effect and structural damping ratios are shown to have significant influence on system dynamic response. In addition, the soil inelasticity is shown to be highly influenced by the magnitude of seismic motion. Both effects are important for validation as they contribute to sensitivity of response to parametric variability. Validation effort described here extends validation approach promoted by Oberkampf and Roy (2010) to civil engineering problems and follows on detailed verification presented earlier (Feng et al., 2019;Tasiopoulou et al., 2015).